2013
DOI: 10.1371/journal.pone.0081947
|View full text |Cite|
|
Sign up to set email alerts
|

PLGA-Carbon Nanotube Conjugates for Intercellular Delivery of Caspase-3 into Osteosarcoma Cells

Abstract: Cancer has arisen to be of the most prominent health care issues across the world in recent years. Doctors have used physiological intervention as well as chemical and radioactive therapeutics to treat cancer thus far. As an alternative to current methods, gene delivery systems with high efficiency, specificity, and safety that can reduce side effects such as necrosis of tissue are under development. Although viral vectors are highly efficient, concerns have arisen from the fact that viral vectors are sourced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 58 publications
0
37
0
Order By: Relevance
“…Their results showed that CP3 was able to attach to functionalized CNTs, forming CNT-PLGA-CP3 conjugates. They also observed that this conjugate efficiently transduced cells at dosages as low as 0.05 mg/ml and suppressed cell proliferation up to a week with no further treatments (149).…”
Section: Nanoparticle Drug Delivery In Cancermentioning
confidence: 93%
“…Their results showed that CP3 was able to attach to functionalized CNTs, forming CNT-PLGA-CP3 conjugates. They also observed that this conjugate efficiently transduced cells at dosages as low as 0.05 mg/ml and suppressed cell proliferation up to a week with no further treatments (149).…”
Section: Nanoparticle Drug Delivery In Cancermentioning
confidence: 93%
“…The degradation rate of the surface polymer allowed the tuning of the siRNA release from the vector. Cheng et al [66] designed a poly-(lactic-co-glycolic acid) (PLGA) functionalized MWCNTs that assisted in the slow release of caspase-3 into osteosarcoma cells upon the enzymatic degradation of PLGA. Non-covalent linking of siRNA with CNTs has an advantage over simple chemical modifications.…”
Section: Cancer Therapymentioning
confidence: 99%
“…By functionalizing single wall carbon nanotube (SWCN) with poly (lactic‐co‐glycolic) acid (PLGA) to achieve high solubility and low cytotoxicity, Cheng et al used PLGA‐SWCN as a carrier to deliver caspase‐3 into osteosarcoma cell MG‐63. PLGA was degraded enzymatically after cellular internalization and released the conjugated caspase‐3 . In addition to polymers, proteins can be adsorbed onto CNT surfaces through van der Waals interactions and hydrophobic interactions to improve dispersability and bio‐compatibility of CNTs .…”
Section: Inorganic Nanocarriers For Anticancer Protein Deliverymentioning
confidence: 99%
“…PLGA was degraded enzymatically after cellular internalization and released the conjugated caspase-3. [ 50 ] In addition to polymers, proteins can be adsorbed onto CNT surfaces through van der Waals interactions and hydrophobic interactions to improve dispersability and bio-compatibility of CNTs. [ 51,52 ] By adsorbing toxin ricin A chain protein (RTA) and a HER2 antibody non-covalently on multi-walled carbon nanotubes (MWNTs), Weng et al selectively targeted HER2 receptors on specifi c breast cancer cells and delivered RTA to its natural intracellular locus to inhibit protein synthesis.…”
Section: Carbon Nanotubesmentioning
confidence: 99%
See 1 more Smart Citation